Capitalism with Chinese characteristics : entrepreneurship and the state - Huang, Yasheng (Cambridge : Cambridge University Press, 2008)
"Since 1978, the Chinese economy has grown phenomenally. Based on archival research and survey data, this book offers this view: Private entrepreneurship, facilitated by access to capital and microeconomic flexibility, was at the center of China's takeoff in the 1980s. The key to getting the China story right is to recognize the existence of two Chinas - an entrepreneurial rural China and a state-controlled urban China."--BOOK JACKET.
Just how capitalist is China? -- The entrepreneurial decade -- A great reversal -- What is wrong with Shanghai? -- Capitalism with Chinese characteristics.
Includes bibliographical references (p. [321]-338) and index.
Keywords: Capitalism -- China; Rural industries -- China; Entrepreneurship -- China; China -- Economic policy